The Role of Stakeholders in the Management of Islamic Education: A Collaborative Approach to Education Quality - Babun; Hefniy; Nurul Aini; Moh. Wardi (Universitas Nurul Jadid, 2024)
This study aims to examine the role of stakeholder empowerment in Islamic education management at MI Mambaul Ulum Tulupari, an Islamic elementary school in Tiris, Probolinggo. This study explores how collaboration between parents, teachers, and the community can improve the quality of education based on Islamic values. Although stakeholder involvement in education has been widely discussed, its application in the context of Islamic education is still limited. Therefore, this study seeks to fill this gap by investigating the active contribution of each stakeholder in designing, implementing, and evaluating education policies in schools. Using qualitative research methods, data was collected through interviews, observations, and documentation. The results of the study show that close collaboration between parents, teachers, and the community plays a significant role in improving the quality of education, both in academic aspects and in the formation of students' character. These findings make an important contribution to the development of more inclusive and sustainable Islamic education management, and emphasize the importance of the active role of all stakeholders in creating a holistic education that is in accordance with Islamic values.